Zero Indirect Band Gap and Flat Bands in a Niobium Oxyiodide Cluster Material - Jan Beitlberger; Mario Martin; Marcus Scheele; Marek Matas; Carl P. Romao; Markus Ströbele; H.-Jürgen Meyer (Journal of the American Chemical Society, 2026)
Abstract Explorative chemistry in a reaction system composed of NbI4, Li2(CN2), and Li2O has led to the discovery of a number of niobium oxyiodide cluster compounds. During this reaction, the formation of solid phases was detected alongside gaseous phases, resulting in a range of products with cluster cores of varying shapes. After several niobium oxyiodide cluster compounds have already been identified within this reaction system, two additional compounds, Nb6O3I15 and Nb11O6I24, are discovered and structurally characterized by single-crystal X-ray diffraction. Both structures are based on the butterfly-shaped, oxygen-capped niobium cluster [Nb4O], which is extended to larger cluster fragments. The [Nb4O] cluster core in Nb6O3I15 is extended by two [NbO] units to form a three-dimensional framework, and Nb11O6I24 contains two connected [Nb4O] units, which form chiral units within an antiferrochiral hexagonal packing of strings. The striking string-like character of Nb11O6I24 was investigated in terms of its electronic structure and properties. DFT calculations showed Nb11O6I24 to possess a zero indirect band gap, with a pair of 3-dimensional flat bands surrounding the Fermi level. These unusual features of the electronic band structure suggest the presence of strongly correlated intercluster singlet electron states, arising from the helical shape of the clusters, the hexagonal packing of the strings, and the delocalized nature of cluster electron wave functions.